Research on the development of warship network technology and its trend prospect - WU Jianlu, XU Zelin, FU Mingju (Zhihui kongzhi yu fangzhen, 2025)
As an important part of ship information infrastructure, the technical development of ship network is of great significance to enhance the combat effectiveness of ship equipment. This paper describes the concept and connotation of warship network. Based on the analysis of the developments and main trends of warship network technology in the United States, combined with the development needs of warship equipment, the development trend of warship network technology is prospected from the aspects of network intelligence, deterministic guarantee and security improvement, which can provide useful reference for the development and efficiency improvement of warship network technology.